Influence of crowding and surfaces on protein amyloidogenesis: A thermo-kinetic perspective - Menon, Sneha; Sengupta, Neelanjana (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2019)
The last few decades have irreversibly implicated protein self-assembly and aggregation leading to amyloid fibril formation in proteopathies that include several neurodegenerative diseases. Emerging studies recognize the importance of eliciting the pathways leading to protein aggregation in the context of the crowded intracellular environment rather than in conventional in vitro conditions. It is found that crowded environments can have acceleratory as well as inhibitory effects on protein aggregation, depending on the interplay of underlying factors on the crucial rate limiting steps. The aggregation mechanism and transient species formed along the pathway are further altered when they interface with natural and artificial surfaces in the cellular milieu. An increasing number of studies probe the autocatalytic nature of amyloid surfaces as well as membrane bilayer effects on amyloidogenesis. Moreover, exposure to modern nanosurfaces via nanomedicines and other sources potentially invokes beneficial or deleterious biological response that needs rigorous investigation. Mounting evidences indicate that nanoparticles can either promote or impede amyloid aggregation, spurring efforts to tune their interactions for developing effective anti-amyloid strategies. Mechanistic insights into nanoparticle mediated aggregation pathways are therefore crucial for engineering anti-amyloid nanoparticle strategies that are biocompatible and sustainable. This review is a compilation of studies that contribute to the current understanding of the altering effects of molecular crowding as well as natural and artificial surfaces on protein amyloidogenesis.